Pellets - en framtidsmarknad? - Anderzén, Erik; Lönnqvist, Wilhelm (2011)
With higher prices for oil and increased focus on fossil fuels impact on the environment the heating sector are searching for alternative fuels. Pellets are a quite new product whose production has risen exponential in recent years. Today there are small-, medium-and large-scale users, where the large-scale consumers are the heating sector. The heating sector is mainly using oil to cover the increased demand during cold periods. The purpose of this study is to analyze the potential of pellets if it would replace thermal power plants oil and coal. The study will also analyze the economic impact a conversion would mean for a heating plant and if the pellet is a reasonable substitute. 2008 statistics from the Swedish district heating association were analyzed and a calculation was performed to determine how many tons of pellets is needed to replace coal and oil. Fuel costs for oil and coal were compared with the costs to produce the equivalent amount of heat with pellets. In order to analyze the economic impact an investment calculation was made. The payback period was calculated for a new wood powder boiler if it was to replace an existing oil boiler. The study includes a qualitative research interview, which was addressed to the largest users of fuel oil and coal for district heating. Policy influences and the heat plant's environmental policy will lead to a gradually phasing out of fossil fuels. The greatest compliment to the non-renewable energy is biofuel where pellets are a possible substitute. A pellets-consuming wood powder boiler can replace the fossil fuel consumption. The readjustment will lead to a great investment and requires that the energy sector prioritize pellets ahead of other alternative fuels.